Neuroprotective Effect of Astersaponin I against Parkinson's Disease through Autophagy Induction - Zhang, Lijun; Park, Jeoung Yun; Zhao, Dong; Kwon, Hak Cheol; Yang, Hyun Ok (KOREAN SOC APPLIED PHARMACOLOGY, 2021)
An active compound, triterpene saponin, astersaponin I (AKNS-2) was isolated from Aster koraiensis Nakai (AKNS) and the autophagy activation and neuroprotective effect was investigated on in vitro and in vivo Parkinson's disease (PD) models. The autophagy-regulating effect of AKNS-2 was monitored by analyzing the expression of autophagy-related protein markers in SHSY5Y cells using Western blot and fluorescent protein quenching assays. The neuroprotection of AKNS-2 was tested by using a 1-methyl-4-phenyl-2,3-dihydropyridium ion (MPP+)-induced in vitro PD model in SH-SY5Y cells and an MPTP-induced in vivo PD model in mice. The compound-treated SH-SY5Y cells not only showed enhanced microtubule-associated protein 1A/1B-light chain 3-II (LC3-II) and decreased sequestosome 1 (p62) expression but also showed increased phosphorylated extracellular signal-regulated kinases (p-Erk), phosphorylated AMP-activated protein kinase (p-AMPK) and phosphorylated unc-51-like kinase (p-ULK) and decreased phosphorylated mammalian target of rapamycin (p-mTOR) expression. AKNS-2-activated autophagy could be inhibited by the Erk inhibitor U0126 and by AMPK siRNA. In the MPP+-induced in vitro PD model, AKNS-2 reversed the reduced cell viability and tyrosine hydroxylase (TH) levels and reduced the induced alpha-synuclein level. In an MPTP-induced in vivo PD model, AKNS-2 improved mice behavioral performance, and it restored dopamine synthesis and TH and alpha-synuclein expression in mouse brain tissues. Consistently, AKNS-2 also modulated the expressions of autophagy related markers in mouse brain tissue. Thus, AKNS-2 upregulates autophagy by activating the Erk/mTOR and AMPK/mTOR pathways. AKNS-2 exerts its neuroprotective effect through autophagy activation and may serve as a potential candidate for PD therapy.